Aztecs, Moors, and Christians Festivals of Reconquest in Mexico and Spain - Harris, Max (University of Texas Press, 2021)
In villages and towns across Spain and its former New World colonies, local performers stage mock battles between Spanish Christians and Moors or Aztecs that range from brief sword dances to massive street theatre lasting several days. The festival tradition officially celebrates the triumph of Spanish Catholicism over its enemies, yet this does not explain its persistence for more than five hundred years nor its widespread diffusion. In this insightful book, Max Harris seeks to understand Mexicans' "puzzling and enduring passion" for festivals of moros y cristianos. He begins by tracing the performances' roots in medieval Spain and showing how they came to be superimposed on the mock battles that had been a part of pre-contact Aztec calendar rituals. Then using James Scott's distinction between "public" and "hidden transcripts," he reveals how, in the hands of folk and indigenous performers, these spectacles of conquest became prophecies of the eventual reconquest of Mexico by the defeated Aztec peoples. Even today, as lively descriptions of current festivals make plain, they remain a remarkably sophisticated vehicle for the communal expression of dissent